Global and regional sepsis and infectious syndrome mortality in 2019: a systematic analysis. (March 2022) - Gray, Authia; Sharara, Fablina
Abstract: Background: Infections can lead to sepsis, a life-threatening reaction in which a dysregulated host response to the infection leads to organ dysfunction. Infectious syndromes can be either infectious underlying causes of death, or intermediate causes of death leading to sepsis. Therefore, infections participate in the cause-of-death chain of communicable, maternal, neonatal, and nutritional diseases, non-communicable diseases, and injuries. Infectious syndromes contribute substantially to global mortality, but data are scarce and neither sepsis nor infectious syndromes are included in standard Global Burden of Disease, Injuries, and Risk Factors Study estimates. Therefore, accurate estimates of infectious syndromes burden are needed to improve health-care policies. Methods: We used 126 million individual death records from multiple causes of death, hospital, linkage, and mortality surveillance data covering 16 countries. Our analysis captures infectious syndromes in the blood, bone, heart, CNS, peritoneum, abdomen, respiratory system, skin, urogenital system, and other locations, as well as specific diseases such as tuberculosis, gonorrhoea, chlamydia, and salmonella infections. We assigned each record an infectious syndrome on the basis of the causes-of-death chain. Through a mixed-effects binomial logistic regression, we calculated infectious syndrome mortality fractions in 2019 by underlying Global Burden of Disease cause, age group, sex, and location, and multiplied on the sepsis mortality envelope in 2019 to obtain attributable deaths. Findings: In 2019, 13·7 million people worldwide died from infectious syndromes, 5·2 million of which co-occurred with non-communicable diseases. 3 million of these deaths occurred in children under the age of 5 years. Globally, respiratory infections and bloodstream infections are the deadliest. Regional disparities are stark, with a death rate of 52·6 per 100 000 for bloodstream infections in sub-Saharan Africa, compared with 37·7 per 100 000 in high-income countries. The burden varies across age groups: adults aged 50–69 years face the highest burden from bloodstream infections, whereas children under the age of 5 years are most burdened by respiratory infections. Interpretation: In 2019, infectious syndromes contributed substantially to mortality, especially in non-communicable disease. Infectious syndrome mortality rivalled ischemic heart disease (9 million deaths) and neoplasms (10 million deaths), suggesting that infections, both as underlying and intermediate causes, are an immense source of mortality and must be recorded, analysed, and treated. Funding: Bill & Melinda Gates Foundation, Wellcome Trust, and Fleming Fund.